GIS-based analysis of the fate of waste-related pathogens Cryptosporidium parvum, Giardia lamblia and Escherichia coli in a tropical canal network - Mamadou B C Diallo (2018)
Urban canals play a major socio-economic role in many tropical countries and, particularly, Thailand. One of the overlooked functions that they perform is a significant attenuation of waste-related pathogens posing considerable health risk, as well as pollution attenuation in general. The study dealt with a comparison of three canals receiving: (i) municipal, (ii) mainly industrial and (iii) mainly agricultural wastewater, listed in order of progressively decreasing organic loading. The occurrence and fate of waterborne Cryptosporidium parvum, Giardia lamblia and Escherichia coli were monitored in the canals by both real-time PCR and conventionally for 12 months. The pathogens are etiological agents of an estimated 38% and 47% of diarrhea cases worldwide and in Thailand, respectively. The geographic information system (GIS) was used to evaluate and map point and, particularly, non-point pollution sources which allowed differentiating the canal sections in terms of predominant pathogen sources. The flowthrough canals, which can be viewed as waste stabilization ponds, were found to be efficiently removing the pathogens at the following generalized specific rates: 0.3 (C. parvum), 1.2 (G. lamblia), 1.8 (E. coli ) log10/km.d in the dry season. The rates decreased in the rainy season for E. coli and G. lamblia, but increased for C. parvum which indicated different removal mechanisms. Data suggest that E. coli and G. lamblia were mainly removed through sedimentation and sunlight (UV) irradiation, while the likely mechanism for C. parvum was predation. Overall, the specific pathogen removal rates positively correlated with the canal organic loading rates in the rainy season. As an important result, an estimate of the municipal pollution mitigation by over 2,280km canals in the Greater Bangkok suggests that concomitant to the pathogens at least 36-95 tons of BOD5 is being removed daily, thereby saving the receiving Chao Phraya River and Bight of Bangkok, by far exceeding current, from major eutrophication problems. © IWA Publishing 2009.